2017
DOI: 10.5194/tc-11-1213-2017
|View full text |Cite
|
Sign up to set email alerts
|

Properties of black carbon and other insoluble light-absorbing particles in seasonal snow of northwestern China

Abstract: Abstract. A large field campaign was conducted and 284 snow samples were collected at 38 sites in Xinjiang Province and 6 sites in Qinghai Province across northwestern China from January to February 2012. A spectrophotometer combined with chemical analysis was used to measure the insoluble light-absorbing particles (ILAPs) and chemical components in seasonal snow. The results indicate that the cleanest snow was found in northeastern Xinjiang along the border of China, and it presented an estimated black carbon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 90 publications
7
74
1
Order By: Relevance
“…Therefore, the second factor or source profile is easily interpretable as a natural soil dust source. But a notable feature is that the relative high mass loading of C BC max (76.4%) to that of the previously identified soil dust source as reported by Pu et al (2017). It is well known that K + and K Biosmoke are the 5 major indicators of biomass burning source (Zhang et al, 2013a).…”
Section: Source Apportionmentmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, the second factor or source profile is easily interpretable as a natural soil dust source. But a notable feature is that the relative high mass loading of C BC max (76.4%) to that of the previously identified soil dust source as reported by Pu et al (2017). It is well known that K + and K Biosmoke are the 5 major indicators of biomass burning source (Zhang et al, 2013a).…”
Section: Source Apportionmentmentioning
confidence: 80%
“…In this study, two datasets including the mass concentrations of the chemical components and the ILAPs in snow/ice and the associated uncertainty datasets were used to run the PMF 5.0 model. The details of the techniques have already been illustrated by Hegg et al (2009Hegg et al ( , 2010 and Pu et al (2017). The factor loadings 20 (apportionment of species mass to individual factors) for the 3-factor solution of the source profiles based on the PMF 5.0 model are given in Fig.…”
Section: Source Apportionmentmentioning
confidence: 99%
“…For the glaciers except BS, the absorption by goethite was larger than BC and approximately equal to organic matters. The increased contribution by goethite at the shorter wavelength was due to its large AAE 5 value (Zhou et al, 2017), which indicated stronger light absorption at short wavelength. While the relative contribution to absorption by hematite appeared to be constant between different wavelengths.…”
Section: Contribution To Light Absorption By Cryoconite Components 10mentioning
confidence: 99%
“…The light attenuation by samples on filter at specific wavelength will be converted to equivalent BC mass loading (L BC , µg C cm -2 ), which allows to calculate absorption optical depth τ(λ) by cryoconite: τ λ =L BC β λ . Where β λ is mass absorption coefficiency (MAC) of standard black carbon (i.e., fullerene, 6.3 m 2 g -1 at 550 nm) (Grenfell et al, 2011;Zhou et al, 2017). Then the light absorption capacity of cryoconite was calculated through 10 dividing the absorption optical depth by the mass loading on filter:…”
Section: Light Absorption Of Cryoconitementioning
confidence: 99%
See 1 more Smart Citation